2006
DOI: 10.1523/jneurosci.5148-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Gain of Rod-Mediated Signals in the Mammalian Retina

Abstract: Effective sensory processing requires matching the gain of neural responses to the range of signals encountered. For rod vision, gain controls operate at light levels at which photons arrive rarely at individual rods, light levels too low to cause adaptation in rod phototransduction. Under these conditions, adaptation within a conserved pathway in mammalian retina maintains sensitivity as light levels change. To relate retinal signals to behavioral work on detection at low light levels, we measured how backgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
216
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(232 citation statements)
references
References 66 publications
15
216
0
1
Order By: Relevance
“…Instead, Mbs synapse directly onto GCs (Marc and Liu 2000;Palmer 2010;Witkovsky and Dowling 1969). Interestingly, the scotopic threshold, or, in other words, the minimal stimulus intensity that activated dark-adapted mouse RBCs, was found to be ϳ0.03 rhodopsin photoisomerization (Rh*)/rod (Dunn et al 2006;Saszik et al 2002). This stimulus intensity is the equivalent of 0.07 photons· m Ϫ2 ·s Ϫ1 presented for 500 ms (Pang et al 2004) and is similar to the scotopic threshold of Mb signaling (Fig.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Instead, Mbs synapse directly onto GCs (Marc and Liu 2000;Palmer 2010;Witkovsky and Dowling 1969). Interestingly, the scotopic threshold, or, in other words, the minimal stimulus intensity that activated dark-adapted mouse RBCs, was found to be ϳ0.03 rhodopsin photoisomerization (Rh*)/rod (Dunn et al 2006;Saszik et al 2002). This stimulus intensity is the equivalent of 0.07 photons· m Ϫ2 ·s Ϫ1 presented for 500 ms (Pang et al 2004) and is similar to the scotopic threshold of Mb signaling (Fig.…”
Section: Discussionsupporting
confidence: 55%
“…The mammalian retina utilizes a dedicated circuitry for processing light signals around the absolute visual threshold, the rod¡RBC¡AII amacrine¡cone BC¡GC pathway (Bloomfield and Dacheux 2001), which allows for gain control/amplification at multiple stages (Schwartz and Rieke 2013). AII amacrine cells amplify RBC output, set the visual threshold for GCs, and also provide a gain control mechanism to ensure luminance encoding over a wide range of light intensities (Arman and Sampath 2012;Dunn et al 2006). However, the fish retina does not have an AIIequivalent cell that collects outputs of dozens of Mbs and amplifies the signal before forwarding it toward GCs.…”
Section: Discussionmentioning
confidence: 99%
“…Different adaptational mechanisms set in at different time points following stimulation. Examples for rather slow mechanisms are changes in the signal amplification of the phototransduction cascade and certain changes in the gain of synaptic transmission 33,34 . In contrast, HCN1 channel feedback provides a rapid adaptational mechanism that affects rod photoreceptor signals just past the leading edge.…”
Section: Discussionmentioning
confidence: 99%
“…Second, Dunn et al (2006) found that there was an approximately twofold increase in noise in the absence of electrical coupling when they compared visual responses of AII amacrines in wild-type and Cx36 KO mice. Hampson et al (1992) suggested that the effects of dopamine and dopaminergic agonists and antagonists on the extent of tracer coupling of AII amacrines were mediated by changes in the phosphorylation of the connexin(s) involved and that the reduction of coupling was mediated by D1-type dopamine receptors and activation of the cAMP -PKA pathway.…”
Section: Functional Role Of Modulating Electrical Coupling Between Aimentioning
confidence: 99%